To find the sum of -8 2/9 and 1 1/6, we first need to convert the mixed numbers into improper fractions.
-8 2/9 = - (8 * 9 + 2)/9 = -74/9
1 1/6 = (1 * 6 + 1)/6 = 7/6
Now, we can add the two fractions:
-74/9 + 7/6 = (-74 * 6 + 7 * 9) / (9 * 6) = (-444 + 63) / 54 = -381/54
To simplify this fraction, we can divide the numerator and denominator by their greatest common divisor, which is 9:
-381/54 = (-381/9) / (54/9) = -127/18
Therefore, the sum of -8 2/9 and 1 1/6 is -127/18, which can be written as -7 1/18.
So, the correct answer is A. -7 1/18.
-8 2/9 + 1 1/6
A. -7 1/18
B. 7 1/18
C. 9 7/18
D. -9 7/18
1 answer